Optimal Control of Holding Motion by Nonprehensile Two-Cooperative-Arm Robot. (14th September 2016) - Jiang, Changan; Nakatomi, Yuta; Ueno, Satoshi
Abstract : Recently, more researchers have focused on nursing-care assistant robot and placed their hope on it to solve the shortage problem of the caregivers in hospital or nursing home. In this paper, a nonprehensile two-cooperative-arm robot is considered to realize holding motion to keep a two-rigid-link object (regarded as a care-receiver) stable on the robot arms. By applying Newton-Euler equations of motion, dynamic model of the object is obtained. In this model, for describing interaction behavior between object and robot arms in the normal direction, a viscoelastic model is employed to represent the normal forces. Considering existence of friction between object and robot arms, LuGre dynamic model is applied to describe the friction. Based on the obtained model, an optimal regulator is designed to control the holding motion of two-cooperative-arm robot. In order to verify the effectiveness of the proposed method, simulation results are shown.